Alcohol consumption and breast cancer risk in Japan: A pooled analysis of eight population‐based cohort studies. Issue 11 (10th February 2021) - Iwase, Madoka; Matsuo, Keitaro; Koyanagi, Yuriko N. Y.; Ito, Hidemi; Tamakoshi, Akiko; Wang, Chaochen; Utada, Mai; Ozasa, Kotaro; Sugawara, Yumi; Tsuji, Ichiro; Sawada, Norie; Tanaka, Shiori; et al.
Abstract: Although alcohol consumption is reported to increase the incidence of breast cancer in European studies, evidence for an association between alcohol and breast cancer in Asian populations is insufficient. We conducted a pooled analysis of eight large‐scale population‐based prospective cohort studies in Japan to evaluate the association between alcohol (both frequency and amount) and breast cancer risk with categorization by menopausal status at baseline and at diagnosis. Estimated hazard ratios (HR) and 95% confidence intervals were calculated in the individual cohorts and combined using random‐effects models. Among 158 164 subjects with 2 369 252 person‐years of follow‐up, 2208 breast cancer cases were newly diagnosed. Alcohol consumption had a significant association with a higher risk of breast cancer in both women who were premenopausal at baseline (regular drinker compared to nondrinker: HR 1.37, 1.04‐1.81, ≥23 g/d compared to 0 g/d: HR 1.74, 1.25‐2.43, P for trend per frequency category: P = .017) and those who were premenopausal at diagnosis (≥23 g/d compared to 0 g/d: HR 1.89, 1.04‐3.43, P for trend per frequency category: P = .032). In contrast, no significant association was seen in women who were postmenopausal at baseline or at diagnosis, despite a substantial number of subjects and long follow‐up period. Our results revealed that frequent and high alcohol consumption are both risk factors for Asian premenopausal breast cancer, similarly to previous studies in Western countries. The lack of a clear association in postmenopausal women in our study warrants larger investigation in Asia. Abstract : What's new? While alcohol consumption is a well‐established risk factor for breast cancer in European populations, associations are less clear for Asian populations. Here, pooled analysis of data for more than 150, 000 Japanese women showed that both high frequency alcohol consumption and consumption of large amounts of alcohol are associated with increased breast cancer risk in premenopausal but not postmenopausal women. Associations were evident especially among women who were premenopausal at diagnosis, compared to women who were premenopausal at baseline. Although further study is needed, the findings indicate that among Asian women, alcohol consumption and breast cancer risk have specific associations.